2002
DOI: 10.1192/bjp.180.5.411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on depressive symptoms in older adults with poorly responsive depressive disorder

Abstract: Because exercise was associated with a modest improvement in depressive symptoms at 10 weeks, older people with poorly responsive depressive disorder should be encouraged to attend group exercise activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
277
0
28

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(330 citation statements)
references
References 21 publications
7
277
0
28
Order By: Relevance
“…the levels of anxiety and/or depression and physical activity showed an inverse relationship. These data are in agreement with several studies which reported that exercise promotes a reduction of symptoms of anxiety and depression 3,[9][10][11][12][13][14][15][16][17][18][27][28][29][30][31][32][33] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…the levels of anxiety and/or depression and physical activity showed an inverse relationship. These data are in agreement with several studies which reported that exercise promotes a reduction of symptoms of anxiety and depression 3,[9][10][11][12][13][14][15][16][17][18][27][28][29][30][31][32][33] .…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have demonstrated that adhesion to a regular program of physical exercises could improve significantly the cognitive performance of an elderly, increasing its self-esteem, humor, feeling of well-being, promoting a reduction of physiological responses to stress and positive effects on body image, therefore reducing levels of anxiety and depression [9][10][11][12][13][14][15][16][17][18] . However, in their study, Bailey and McLaren 19 did not find any significant positive relationship between improvement in anxiety and depression and physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Evidence from controlled studies on carefully selected depressed adults and older adults suggest that exercise training improves depressive symptoms in the short term. [23][24][25][26][27][28][29] Prompted by the promise of health benefits with physical activity, many organizations, including health plans, have in recent years expanded their prevention benefits to include formal physical activity programs. Because such benefits can be costly to finance, decision makers need information on who actually use these benefits, barriers associated with use, and what pattern of use results in improved outcomes at the population level.…”
Section: Introductionmentioning
confidence: 99%
“…A linearly reduced risk of depression by physical activity physical activity moderates depressive symptoms-disabilityhas been observed (Strawbridge et al, 2002), the effect pertaining to at least a moderate amount of exercise or recreational activity (Farmer et al, 1988;Camacho et al, 1991). Clinical trials involving older adults lend support to the efficacy of exercise training in reducing depressive symptoms (Mather et al, 2002;Barbour and Blumenthal, 2005). Various hypotheses have been raised on physical activity's mental health benefit, including increased self-efficacy, mastery, social interaction, and brain synaptic aminergic transmissions (Paluska and Schwenk, 2000).…”
Section: Discussionmentioning
confidence: 99%